Switzerland : Financial Sector Assessment Program; Technical Note; Insurance Sector Stress Testing. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This technical note discusses key findings of the insurance sector stress tests for Switzerland. The results suggest that there are market risks inside some Swiss insurance entities that may need focused attention. In particular, a moderate correction in share and property values, with interest rates ending somewhat lower than the prior cyclical lows, could cause distress to five out of nine life insurers, two of 12 nonlife insurers, and two of nine health insurers that participated in the 2006 Swiss Solvency Test (SST) field tests.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet